Indirect Tax and Economic Growth - Rayamajhi Sushma (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2022)
The study investigates the empirical relationship between indirect taxes and economic growth in Neal. For estimation, the annual time series data (1975 to 2022) was used. The main purpose of the research is to find the long-run and short-run relationship between indirect taxes and economic growth. Augmented Dickey fuller unit root tests were used to check the stationarity of every variable in the study. Auto Regressive Distributed Lag (ARDL) bounds testing approach for co integrations (developed in 2001) was applied to estimate the long-run and short-run relationship among the variables. Indirect taxes have negative and significant effect on economic growth in long-run while its coefficients in short-run were insignificant.